KETERKAITAN PERILAKU BERKELOMPOK PETANI DENGAN PRODUKTIFITAS PADI (PERBANDINGAN KASUS DI KARAWANG DAN INDRAMAYU) - Rasmikayati, Elly; Wiyono, Sulistyodewi Nur; Saefudin, Bobby Rachmat (Agros Journal of Agriculture Science, 2024)
Rice is a superior commodity which is the people's basic food need, so demand continues to increase from year to year. The government is trying to continue to encourage rice production in response to this growing need. However, national rice production in 2023 will experience a decline from the previous year. On the other hand, at the provincial level, West Java rice production has actually increased with the largest contributors being Indramayu and Karawang Regencies. This research aims to identify the characteristics of farmers and compare differences in farmer group behavior in two rice production centers in West Java in relation to rice productivity. The research methods used are cross tabulation, difference tests, and parametric and non-parametric correlation tests. Respondent selection used a two-stage stratified sampling technique. The sample for this research was 45 Indramayu rice farmers and 54 Karawang rice farmers. The research results show that the characteristics of farmers in both districts are that the majority are aged 46–56 years, have elementary school education, have been rice farmers for 17–24 years and have rice fields of 1 hectare or more. Meanwhile, the group behavior of Indramayu and Karawang farmers has significant differences, but the group behavior of farmers has no relationship with rice productivity in production centers in West Java. Key-words: farmer group behavior, productivity, rice